Analiza odcisków tkanin na IX-XI-wiecznej ceramice naczyniowej z Góry, gm. Pobiedziska, woj. wielkopolskie, stan. 1 - Sikorski, Andrzej (Folia Praehistorica Posnaniensia, 2018)
Results of the analysis of fabrics impressions on pottery brings about a valuable information about materials used in potter’s workshops. It seems that old rags were most commonly used there. Craftsmen employed them for the following purposes: (a) to get a molded vessel unstuck from pad and/or wheel (the rag was put under the bottom - possibly instead of filling); (b) to smooth vessel’s surface (after it has been formed); (c) to carry finished, albeit still soft pot; (d) to put a drying vessel on the fabric. A study of “pottery” fabrics, often completely ignored by scholars, is not of trivial importance for the reconstruction of textile products, not only in the Middle Ages.